Son [videorecording (DVD)] - Dardenne, Jean-Pierre, 1951-; Dardenne, Jean-Pierre, 1951-; Dardenne, Jean-Pierre, 1951-; Dardenne, Luc, 1954-; Dardenne, Luc, 1954-; Dardenne, Luc, 1954-; Gourmet, Olivier; Marinne, Morgan; Soupart, Isabella (New Yorker Video, 2004)
Oliver is working as a carpentry instructor in a French suburb. He develops an obsession with a new student and offers him friendship and advice with a frightening lack of affection. Oliver's connection to the boy is slowly and painfully revealed.